Association Between the "We Can Do This" Campaign and COVID-19 Booster Uptake, U.S., 2021-2022 - Benjamin Denison, MA, PhD; Morgane Bennett, MPH, DrPH; Jae-Eun Kim, MA, PhD; Heather Dahlen, MA, PhD; Christopher Williams, MA, PhD; Joseph N. Luchman, PhD; Elissa C. Kranzler, MSEd, MA, PhD; Sarah Trigger, MPH; Tyler Nighbor, PhD; Michael C. Marshall, PhD; Leah Hoffman, MPH (Elsevier, 2024)
Introduction: Monovalent COVID-19 boosters lower the risk of COVID-19 disease, infection, hospitalization, and death. This study examined associations between exposure to a booster public education campaign (the booster campaign) and the increases in booster uptake and reduced length of time until booster uptake among U.S. adults. Methods: Data included a national survey panel of U.S. adults and booster campaign paid media (i.e., digital impressions and TV gross rating points) from September 2021 to May 2022. Multilevel logistic regression models examined the association between exposure to the booster campaign and the likelihood of booster uptake. A Cox proportional hazard model evaluated the association between the booster campaign and booster uptake timing. Interaction terms between the booster campaign media variables and first-dose COVID-19 vaccine date examined differential effects of the booster campaign based on when individuals received their first dose. Results: Interactions between first-dose vaccination date and the booster campaign were statistically significant for cumulative digital impressions (ß=4.75e-08; 95% CIs=5.93e-09, 8.90e-08) and TV gross rating points (ß = 4.62e-05; 95% CIs=5.09e-06, 8.73e-05), suggesting that booster uptake was strongest among those who received their first-dose COVID-19 vaccine later. Booster campaign cumulative digital impressions and TV gross rating points were associated with accelerated booster uptake among those with later first-dose vaccination dates (digital: ß=9.98e-08; 95% CIs=2.70e-08, 1.73e-07; TV: ß=0.0001; 95% CIs=2.80e-05, 0.0002), relative to those with earlier first-dose vaccination dates. Conclusions: The booster campaign may have increased monovalent booster uptake and reduced how long individuals waited until getting their booster. Public education campaigns show promise in stemming the tide of pandemic fatigue and increasing booster confidence.